Molecular Dynamics Study of the Antifouling Mechanism of Hydrophilic Polymer Brushes - Yagasaki, Takuma (Langmuir : the ACS journal of surfaces and colloids, 2023)
We perform all-atom molecular dynamics simulations of the adsorption of amino acid side-chain analogues on polymer brushes. The analogues examined are nonpolar isobutane, polar propionamide, negatively charged propionate ion, and positively charged butylammonium ion. The polymer brushes consist of a sheet of graphene and strongly hydrophilic poly(carboxybetaine methacrylate) (PCBMA) or weakly hydrophilic poly(2-hydroxyethyl methacrylate) (PHEMA). The effective interactions between isobutane and polymer chains are repulsive for PCBMA and attractive for PHEMA. Gibbs energy decomposition analysis shows that this is due to the abundance of water in the PCBMA brush, which increases the steric repulsion and decreases the Lennard-Jones attraction. The affinity of the hydrophilic analogues is low for both PCBMA and PHEMA chains, but the balance between the components of the Gibbs energy is different for the two polymers. The simulations are performed at several θ, where θ is the degree of overlap of polymer chains. The antifouling performance against the neutral analogues is better for PCBMA than for PHEMA in the low and high θ regimes. However, in the middle θ regime, the antifouling performance of PHEMA is close to or better than that of PCBMA. This is attributed to the formation of a dense layer of PHEMA on the graphene surface that inhibits direct adsorption of analogue molecules on graphene. The charged analogues do not bind to either the PHEMA or PCBMA brush irrespective of θ